Comparison of biochemical and immunological profile of pediatric patients with acute myeloid leukemia in relation to healthy individuals - Fabiane L.F.Z. Sanches; Taís M. Nitsch; Maria Marluce S. Vilela; Valdemiro C. Sgarbieri (Elsevier, 2015)
Objective: To compare the biochemical and immunological profiles of pediatric patients with acute myeloid leukemia (AML) with healthy children and adolescents. Methods: This was a cross-sectional study in which 21 therapy-naïve patients with AML were compared with a group of 24 healthy individuals. The following data were analyzed: serum proteins, leucocytes and subgroups, erythrocytes, hematocrit, hemoglobin, platelets, cytokines in peripheral blood mononuclear cells cultures under spontaneous and BCG- or PHA-stimulated conditions, immunoglobulin A, and erythrocytic glutathione. Statistical analysis was performed using SPSS software, considering as significant p-values < 0.05. Results: Serum albumin levels were higher (p < 0.0001) in the control group, as well as all the parameters related to red blood cells (p < 0.0001). For leucocytes and subgroups, no statistical difference was found between the AML and the control groups. For cytokines, the concentrations were significantly higher under spontaneous and BCG-stimulated conditions for TNF-α, IL-6, IL-10, and IFN-γ in the control group. Under PHA-stimulated conditions, the concentration was higher (p = 0.002) only for IL-6. No difference was found between the two groups for the other cytokines and for IgA in the saliva. Erythrocytic glutathione was higher (p < 0.0001) in AML patients. Conclusions: It was possible to characterize the biochemical and immunological profile of pediatric patients with AML, as well as highlight some significant differences in these parameters when comparing with healthy children and adolescents. Resumo: Objetivo: Comparar o perfil bioquímico e imunológico de pacientes pediátricos portadores de Leucemia Mieloide Aguda (LMA) em relação a um grupo de crianças e adolescentes saudáveis. Métodos: Estudo transversal, em que foram avaliados 21 pacientes com LMA virgens de terapia e um grupo de 24 indivíduos saudáveis. Foram analisadas: proteínas séricas, leucócitos e subgrupos, eritrócitos, hematócrito, hemoglobina e plaquetas, citocinas em cultura de células mononucleares do sangue periférico sob condição espontânea e estimulada por BCG ou PHA, imunoglobulina A e glutationa eritrocitária. Análise estatística foi realizada através do software SPSS considerando p < 0,05. Resultados: Albumina sérica foi superior (p < 0,0001) no grupo de controle, bem como, todos os parâmetros relacionados com os glóbulos vermelhos (p < 0,0001). Para os leucócitos e subgrupos não houve diferença estatística entre os pacientes com LMA e o grupo controle. As concentrações foram significativamente mais elevadas sob condições espontânea e estimulada por BCG para as citocinas TNF-α, IL-6, IL-10 e IFN-γ no grupo controle. Sob condição estimulada com PHA a concentração foi superior (p = 0,002) apenas para a IL-6. Não houve diferença estatística para as demais citocinas e para IgA salivar entre os dois grupos. Glutationa eritrocitária foi superior (p < 0,0001) nos pacientes LMA. Conclusões: Diante do exposto foi possível caracterizar o perfil bioquímico e imunológico de pacientes pediátricos com LMA, bem como, evidenciar diferenças significativas em alguns desses parâmetros ao se comparar os indivíduos doentes e o grupo de crianças e adolescentes saudáveis. Keywords: Pediatrics, Leukemia, Biochemical assessment, Immune evaluation, Palavras-chave: Pediatria, Leucemia Mieloide Aguda, Avaliação Bioquímica, Avaliação Imunológica